2022
DOI: 10.3389/fnut.2022.848532
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Oral Administration of Bamboo (Dendrocalamus membranaceus) Leaf Flavonoids on the Antioxidant Capacity, Caecal Microbiota, and Serum Metabolome of Gallus gallus domesticus

Abstract: The consumption of bamboo leaf flavonoids (BLFs) as novel dietary antioxidants has increased owing to their beneficial biological and pharmacological functions. This study assessed the in vivo effects of BLFs on antioxidant capacity, as well as caecal microbiota, serum metabolome, and health status. The Gallus gallus domesticus model and the oral administration approach were used with four treatment groups (basal diet, basal diet with 20 mg bacitracin/kg, basal diet with 50 mg BLF/kg, and basal diet with 250 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 59 publications
(73 reference statements)
2
10
0
Order By: Relevance
“…Similar to our previous study, the bamboo (Dendrocalamus membranaceus) leaf avonoids were composed of 24.2% avonoids, 12.5% lactones, and 15.6% phenolic acids [22]. Moreover, the major compositions of BLFs are chlorogenic acid (21.33 mg/100 g), caffeic acid (1.85 mg/100 g), orientin (34.66 mg/100 g), isoorientin (34.66 mg/100 g), p-coumaric acid (26.69 mg/100 g), vitexin (148.42 mg/100 g), and fumalic acid (265.03 mg/100 g).…”
Section: Animal Designation and Materialssupporting
confidence: 86%
See 3 more Smart Citations
“…Similar to our previous study, the bamboo (Dendrocalamus membranaceus) leaf avonoids were composed of 24.2% avonoids, 12.5% lactones, and 15.6% phenolic acids [22]. Moreover, the major compositions of BLFs are chlorogenic acid (21.33 mg/100 g), caffeic acid (1.85 mg/100 g), orientin (34.66 mg/100 g), isoorientin (34.66 mg/100 g), p-coumaric acid (26.69 mg/100 g), vitexin (148.42 mg/100 g), and fumalic acid (265.03 mg/100 g).…”
Section: Animal Designation and Materialssupporting
confidence: 86%
“…The present results were in accordance with the previous study [20], that is BLF supplementation improved the ADG of broilers from days 21 to 42. Our previous study also found that BLF pretreatment signi cantly enhances the ADG of birds from days 15 to 21 and 1 to 21 [22]. The components and palatability of BLFs could improve the antioxidant function and growth performance of broilers [24].…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…Ages, d Similar to our previous study, the bamboo (Dendrocalamus membranaceus) leaf flavonoids were composed of 24.2% flavonoids, 12.5% lactones, and 15.6% phenolic acids [23], which were provided by Zhejiang Vegamax Biotechnology Co., Ltd. (Anji, China) and directly added to the basal diet. Moreover, the major compositions of BLFs are chlorogenic acid (21.33 mg/100 g), caffeic acid (1.85 mg/100 g), orientin (34.66 mg/100 g), isoorientin (34.66 mg/100 g), p-coumaric acid (26.69 mg/100 g), vitexin (148.42 mg/100 g), and fumalic acid (265.03 mg/100 g).…”
Section: Itemsmentioning
confidence: 89%